2004
DOI: 10.1002/cm.20031
|View full text |Cite
|
Sign up to set email alerts
|

Geometry drives the “deviated‐bending” of the bi‐tubular structures of the 9+2 axoneme in the flagellum

Abstract: The axoneme "9 + 2" is basically a system constituted of a cylinder of 9 microtubule doublets surrounding a central pair of microtubules. These bi-tubular structures are considered as the support system of the active molecular complexes that generate and regulate the axonemal movement. Schoutens has calculated their moments of inertia [Schoutens, 1994: Journal of Theoretical Biology 171:163-177]. The results obtained allowed us to assume that these bi-tubular systems are endowed with dynamic properties that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
(81 reference statements)
0
9
0
Order By: Relevance
“…In fact, it was observed that the longitudinal constraints regulate the dynamic instability of the microtubules (Janson et al, 2003;Warner, 1976), and that the wall of the microtubule is elastic, because it accumulates energy (Hunyadi et al, 2005). The microtubules oscillate in different modes when they are subjected to an external constraint (Kasas et al, 2004a, b;Kis et al, 2002), and might be involved in a ''deviated bending'' (Cibert and Heck, 2004). The microtubules are clearly force-sensitive, being involved in tensegrity and in the mechanical transduction of a signal (Gundersen and Cook, 1999;Ingber, 1997Ingber, , 2003a, and it is impossible to exclude that they are allosteric effectors (Bray and Duke, 2004).…”
Section: Article In Pressmentioning
confidence: 96%
“…In fact, it was observed that the longitudinal constraints regulate the dynamic instability of the microtubules (Janson et al, 2003;Warner, 1976), and that the wall of the microtubule is elastic, because it accumulates energy (Hunyadi et al, 2005). The microtubules oscillate in different modes when they are subjected to an external constraint (Kasas et al, 2004a, b;Kis et al, 2002), and might be involved in a ''deviated bending'' (Cibert and Heck, 2004). The microtubules are clearly force-sensitive, being involved in tensegrity and in the mechanical transduction of a signal (Gundersen and Cook, 1999;Ingber, 1997Ingber, , 2003a, and it is impossible to exclude that they are allosteric effectors (Bray and Duke, 2004).…”
Section: Article In Pressmentioning
confidence: 96%
“…Also, because the switching mechanism depends on the total stress acting across the axonemal scaffold, imposed external forces that stress the axoneme will also alter the switch-point. Cibert and Heck have suggested that, when the doublets are bent, they also experience a torsional force because they are not radially symmetric (Cibert and Heck, 2004). They suggested that the torsional force might play a role in breaking the dynein attachments and in terminating episodes of activity in a geometric-clutch-type stress-based regulatory scheme.…”
Section: Geometric Clutchmentioning
confidence: 99%
“…Because the orientations of the ODPs are constant during their rotation around the axonemal cylinder, the apparent lengths of the inner and of the outer dynein arms vary in such a way that those of the outer dynein arms are shortened as compared to those of the inner dynein arms (Cibert and Heck, 2004). This mechanism could be involved in the discrimination of the functions of the inner and outer rows of dynein arms (Brokaw, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…The beams that represent the ODPs have a full discoid cross section whose radius equals 8 nm. Their Young modulus and Poisson's ratio are taken from (Schoutens, 1994;Tuszynski et al, 2005); their flexure inertias are given by Schoutens, 1992 andHeck, 2004. Young's modulus is that calculated by Schoutens, 1992. The shear coefficients (k y and k z ) are obtained by considering a hollow cylinder.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation